Comparison of purified psoralen-inactivated and formalin-inactivated dengue vaccines in mice and nonhuman primates. Issue 17 (9th April 2020) - Sundaram, Appavu K.; Ewing, Daniel; Blevins, Maria; Liang, Zhaodong; Sink, Sandy; Lassan, Josef; Raviprakash, Kanakatte; Defang, Gabriel; Williams, Maya; Porter, Kevin R.; Sanders, John W.
Highlights: Two-step purification of Dengue virus using Chromatographic methods. Psoralen-inactivation of Dengue virus. Evaluation of psoralen-inactivated Dengue virus vaccines in mice. Evaluation of psoralen-inactivated Dengue virus vaccines in nonhuman primates. Abstract: Dengue fever, caused by dengue viruses (DENV 1–4) is a leading cause of illness and death in the tropics and subtropics. Therefore, an effective vaccine is urgently needed. Currently, the only available licensed dengue vaccine is a chimeric live attenuated vaccine that shows varying efficacy depending on serotype, age and baseline DENV serostatus. Accordingly, a dengue vaccine that is effective in seronegative adults, children of all ages and in immunocompromised individuals is still needed. We are currently researching the use of psoralen to develop an inactivated tetravalent dengue vaccine. Unlike traditional formalin inactivation, psoralen inactivates pathogens at the nucleic acid level, potentially preserving envelope protein epitopes important for protective anti-dengue immune responses. We prepared highly purified monovalent vaccine lots of formalin- and psoralen-inactivated DENV 1–4, using Capto DeVirS and Capto Core 700 resin based column chromatography. Tetravalent psoralen-inactivated vaccines (PsIV) and formalin-inactivated vaccines (FIV) were prepared by combining the four monovalent vaccines. Mice were immunized with either a low or high dose of PsIV or FIV to evaluate the immunogenicity of monovalent as well as tetravalent formulations of each inactivation method. In general, the monovalent and tetravalent PsIVs elicited equivalent or higher titers of neutralizing antibodies to DENV than the FIV dengue vaccines and this response was dose dependent. The immunogenicity of tetravalent dengue PsIVs and FIVs were also evaluated in nonhuman primates (NHPs). Consistent with what was observed in mice, significantly higher neutralizing antibody titers for each dengue serotype were observed in the NHPs vaccinated with the tetravalent dengue PsIV compared to those vaccinated with the tetravalent dengue FIV, indicative of the importance of envelope protein epitope preservation during psoralen inactivation of DENV.